Total synthesis of the post-translationally modified polyazole peptide antibiotic goadsporin - Dexter, Hannah L.; Williams, Huw E.L.; Lewis, William; Moody, Christopher J. (Wiley-VCH Verlag, 2017)
The structurally unique polyazole antibiotic goadsporin contains six heteroaromatic oxazole and thiazole rings integrated into a linear array of amino acids that also contains two dehydroalanine residues. An efficient total synthesis of goadsporin is reported in which the key steps are the use of rhodium(II)-catalyzed reactions of diazocarbonyl compounds to generate the four oxazole rings, which demonstrates the power of rhodium carbene chemistry in organic chemical synthesis.